Morpholinyl silicon phthalocyanine nanoparticles with lysosome cell death and two-photon imaging functions for in vitro photodynamic therapy of cancer cells - Yu, Hongjie; Chen, Jianling; Chen, Xiuqin; Zhang, Tiantian; Li, Yuyang; Chen, Kuizhi; Peng, Yiru; Chen, Linying (Frontiers in Bioengineering and Biotechnology, 2023)
The lysosome is an important target for realizing antitumor therapy because of the prominent therapeutic effect of lysosomal cell death on apoptosis- and drug-resistance cancer. Development of multifunctional lysosome-targeting nanoparticles for obtaining efficient cancer treatment is a significantly challenging task. In this paper, a morpholinyl silicon phthalocyanine nanoparticles DSPE@M-SiPc possessing bright two-photon fluorescence, lysosome targeting photodynamic therapy functions are prepared by encapsulating M-SiPc in functional amphiphilic polymers. Two photon fluorescence bioimaging showed that M-SiPc and DSPE@M-SiPc mainly locates in lysosomes after cellular internalization. Upon irradiation, DSPE@M-SiPc effectively generates reactive oxygen species, damages the function of lysosome and subsequently leads to lysosomal cell death. This study brings a bovel insight into the development of a superior effective nanophotosentizer for cancer treatment.